Dr. Ryu Hosoi — Deep Plane Facelift — Tokyo - Hosoi, Ryu (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ryu Hosoi, practicing in Tokyo, Japan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003105; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; japan; tokyo